Relation of Psychological anxiety level with ranking list of football clubs Field Study on the second Algerian professionnel league of football - بطاهر محمد; عكوش كمال; سعداوي محمد (Journal of Sport Science Technology and Physical Activities, 2025)
Psychological preparation has an important role in achieving results. Psychological anxiety level is one manifestation of sychological emotions, we try to study the subject of anxiety level and its relation to the ranking list of teams was studied for the Second Algerian professionnel league for the season 2018/2019 of football, we used the scale of anxiety level, we found that the level of anxiety was medium and above average which is normal for the most teams. In addition to the different degrees of levels of anxiety between teams according to the level of psychological preparation for each team. Finaly, we found that the impact of hinder anxiety on players has to do with the ranking list of teams.